Swietenia macrophylla King: ekologi, silvikultur dan produktivitas - Krisnawati, H.; Kallio, M.H.; Kanninen, M. (Center for International Forestry Research, 2011)
This manual gathers information on the ecology and silviculture of Swietenia macrophylla King, with a focus on Indonesia. It also includes growth and yield data from published sources, collected from smallholders’ farms in the research sites in South Kalimantan province, and collected previously by the Forestry Research and Development Agency of Indonesia. This manual is one of five manuals that guide smallholder tree planting of five selected tree species in Indonesia. The other four species are: Acacia mangium Willd.; Aleurites moluccana (L.) Willd.; Anthocephalus cadamba Miq.; and Paraserianthes falcataria (L.) Nielsen. Smallholders in Indonesia have planted trees on private or community land for a long time. Various actors have encouraged this activity with the aim of improving local livelihoods, environmental sustainability and industrial wood supply. Since farmers often lack technical capacity and management know-how, the quality and quantity of products may not be optimal. Productivity of smallholder plantations can be improved by enhancing smallholders’ management knowledge and skills, including species selection based on site matching, silvicultural management to maximise product quality, and pest and disease management.